Numerical FEM Models of Bio-heat Transfer for Magnetic Fluid Hyperthermia Treatments - Febri Dwi Irawati; Agus Kartono (Journal of Multidisciplinary Academic, 2021)
Numerical solutions using the Finite Element Method (FEM) of one-dimensional bio-heat transfer of healthy and cancerous tissue together with the Magnetic Fluid Hyperthermia treatment have been worked out successfully. Each layer shows the characteristics of tissue. Each layer represents an independent biological tissue characterized by temperature-dependent physiological parameters and linear temperature-dependent metabolic heat generation. Magnetic fluid hyperthermia (MFH) is used as an external heat source to heat the cancerous area. In a transient state MFH treatments can heat up cancerous tissue without damaging healthy tissue as indicated by an increase in the temperature of the cancer tissue according to the standard temperature of the MFH treatments.